Case Report: Primary Alveolar Soft Part Sarcoma of the Breast. (9th November 2022) - Abdelmalak, M; Jeck, W; Bentley, R C; Factor, R E; Rosenberger, L H; Peterson, D E
Abstract: Introduction/Objective: Alveolar soft part sarcoma (ASPS) is an exceedingly rare malignant neoplasm, typically arising in the lower limbs or the head and neck region of children and young adults. Very few cases of primary ASPS have been reported arising in the breast. Methods/Case Report: A 16-year-old female presented with a slowly growing mass of the left breast for three years. Clinical and imaging features were initially consistent with a fibroadenoma. Palpable increase in size prompted repeat ultrasound revealing a 3.4 cm oval, complex, cystic and solid mass. Due to its complexity by imaging and interval growth, biopsy was recommended. The biopsy demonstrated a cellular, vascular, and nested tumor consisting of polygonal cells with abundant granular eosinophilic cytoplasm and round nuclei with prominent nucleoli. Tumor cell discohesion and pseudoalveolar growth pattern were also seen in several areas, while necrosis and increased mitoses were not identified. The histologic findings were not consistent with a fibroepithelial lesion. The differential diagnosis included apocrine adenosis, granular cell tumor, melanoma, acinic cell carcinoma and ASPS. By immunohistochemistry, the lesion demonstrated strong and diffuse positivity for TFE3, MyoD1 and desmin. It was negative for pancytokeratin, CD68, S-100, HMB45 and smooth muscle actin. A TFE3 gene rearrangement was detected by FISH. The morphologic, immunohistochemical, and molecular findings were most consistent with ASPS. At resection, the tumor was entirely confined to the breast, with no involvement of the chest wall. No other potential primary sites were found by imaging work-up. Results (if a Case Study enter NA): NA Conclusion: Although ASPS has distinctive histologic and molecular features, it may cause diagnostic dilemmas when arising in unusual sites. Here we report a highly unusual case of a primary ASPS arising in the breast of a teenager, which clinically mimicked a fibroadenoma. While this is a rare entity, it supports the biopsy of any breast mass with interval growth.